Critical Role of Tropical North Atlantic SSTA in Boreal Summer in Affecting Subsequent ENSO Evolution. Issue 8 (16th April 2022) - Jiang, Leishan; Li, Tim; Ham, Yoo‐Geun
Abstract: The season‐dependent impacts of the tropical North Atlantic (TNA) sea surface temperature anomaly (SSTA) on subsequent El Niño‐Southern Oscillation (ENSO) evolution were investigated through observational and modeling studies. The results indicate that, although the maximum amplitude of the TNA SSTA occurs during boreal spring, the TNA SSTA in boreal summer generates a stronger rainfall response in situ, which can further induce a significantly stronger zonal wind anomaly over the equatorial western Pacific via Kelvin and Rossby wave processes. The cause of a stronger precipitation response in boreal summer is attributed to the northward migration of the climatological Atlantic warm pool and the Inter‐Tropical Convergence Zone. Idealized Coupled General Circulation Model experiments further demonstrate that a persisting TNA SSTA forcing up to boreal summer is critical in conveying the TNA impact to subsequent ENSO evolutions in the Pacific. Plain Language Summary: Some recent studies have suggested that the sea surface temperature anomaly (SSTA) over the Tropical North Atlantic (TNA) from boreal spring can influence the El Niño‐Southern Oscillation (ENSO) evolution in the subsequent winter. Observational evidence shows that the TNA SSTA usually peaks during the springtime and decays during the summertime. Therefore, much attention is paid to the boreal spring when investigating the influence of the TNA SSTA on ENSO. However, although the summertime TNA SSTA is weaker than the springtime, due to the Atlantic mean state modulation, the summertime TNA SSTA can induce a stronger rainfall response locally, which can produce a more significant atmospheric response over the equatorial western Pacific to favor the development of the ENSO. Further numerical simulations suggest that the TNA SSTA forcing in boreal summer is crucial in inducing the cold SSTA over the Pacific in the subsequent winter, even though its amplitude is weaker than that in boreal spring. Our results indicate that a special attention should be paid to the amplitude of the summertime TNA forcing in addition to the peak time TNA forcing in boreal spring in real‐time ENSO forecast. Key Points: Tropical North Atlantic sea surface temperature anomaly (TNA SSTA) peaks in boreal spring but the TNA‐induced rainfall anomaly is stronger in boreal summer The stronger summer TNA rainfall response to the weaker TNA SSTA is due to the northward shift of the Atlantic mean warm pool and Inter‐Tropical Convergence Zone The persisting TNA SSTA till boreal summer is crucial in conveying the impact of the TNA SSTA on El Niño‐Southern Oscillation in the subsequent winter